Delineating the Mud Crab Fishery and Marketing Systems: A Case Study from Coastal Andhra Pradesh, India - PALSAM, K.K.G.; PRAKASH, S.; KAMBLE, A.L.; QURESHI, N.W.; YADAV, V.K.; MANISELVAM , J.; THAPA, A. (Journal of the Indian Society of Coastal Agricultural Research, 2025)
This study investigates the production and marketing of wild-caught mud crabs in Andhra Pradesh, focusing on Krishna district as a case study. Purposive and snowball sampling were used to get firsthand information from 80 mud crab fishers, 8 village collectors, and 6 large suppliers. These people were interviewed in person using a structured interview schedule. The study found that mud crab fishing was practiced by three Hindu communities, namely Yanadi, Vaddera, and Agni-Kula Kshatriya. These communities used four different gears, namely bamboo traps, crab lift nets, hooked iron rods, and gill nets, for catching mud crabs. Locals marketed mud crabs in six different grades: XL, Big, M, GL, RB, and RL. In total, six marketing channels were identified, with 65% of the total mud crab supply being export-orientated and the remaining 35% distributed across domestic markets. Marketing cost analysis indicated that local village collectors incurred an average cost of `16.20 kg-1, while large suppliers had a higher cost of `36.73 kg-1, mainly due to transportation, which accounted for 25.20% and 31.50% of the total marketing costs, respectively. The estimated marketing profit was `39.92 kg-1 for local village collectors and `24.27 kg-1 for large suppliers. Strengthening regulations, supporting fishers’ livelihoods, and promoting mud crab aquaculture are crucial to ensure the long-term sustainability and resilience of the mud crab supply chain.